Diagnostic Accuracy of GeneXpert in Pulmonary and Extra-pulmonary Specimens in Tertiary Care Settings of South Punjab - Rashda Shabbir, SM Abbas Naqvi, Javaria Saeed, Guljanan, Shazia Shamas, Sana Rehman (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To determine the diagnostic accuracy of GeneXpert in pulmonary and extra-pulmonary specimens taking LJ media as the gold standard. Study design and settings: This cross sectional study was undertaken in the Provincial Reference TB Laboratory collaboration with Pathology Department, Nishtar Medical University Multan from November 2020-November 2021. Methodology: A total of 210 suspected TB cases of aged 18 years and above were included. Samples from suspects were collected. A pre-designed questionnaire was used to collect demographic information, history, and other required information and samples were processed for culture on LJ medium while second sample was processed for GeneXpert. Data was entered and analyzed in SPSS. Results: A total of 210 patients were enrolled consisting of 113(53.8%) males and 97(46.2%) with overall mean age of patients as 36.81±16.22 years. Sensitivity, specificity, PPV, NPV and accuracy were calculated by taking LJ culture as gold standard remained to be 75.13%, 88.24%, 98.64%, 23.81% & 76.19% for smear and 99.48%, 83.33%, 98.45%, 93.75% and 98.10% respectively for GeneXpert. Conclusion: GeneXpert has been found to be extremely efficient technique in certain diagnosis of TB along provision of rifampicin susceptibility thus, helpful in early indication of MDR TB. Keywords: GeneXpert, Culture on LJ, Tuberculosis, Diagnosis.